Porcine computational modeling to investigate developmental dysplasia of the hip - Yu, Chia‐Yu; Mannen, Erin M.; Lujan, Trevor J.; Uzer, Gunes; Upasani, Vidyadhar; Edmonds, Eric W.; Fitzpatrick, Clare K. (Journal of orthopaedic research, 2024)
While it is well‐established that early detection and initiation of treatment of developmental dysplasia of the hip (DDH) is crucial to successful clinical outcomes, research on the mechanics of the hip joint during healthy and pathological hip development in infants is limited. Quantification of mechanical behavior in both the healthy and dysplastic developing joints may provide insight into the causes of DDH and facilitate innovation in treatment options. In this study, subject‐specific three‐dimensional finite element models of two pigs were developed: one healthy pig and one pig with induced dysplasia in the right hindlimb. The objectives of this study were: (1) to characterize mechanical behavior in the acetabular articular cartilage during a normal walking cycle by analyzing six metrics: contact pressure, contact area, strain energy density, von Mises stress, principal stress, and principal strain; and (2) to quantify the effect on joint mechanics of three anatomic abnormalities previously identified as related to DDH: variation in acetabular coverage, morphological changes in the femoral head, and changes in the articular cartilage. All metrics, except the contact area, were elevated in the dysplastic joint. Morphological changes in the femoral head were determined to be the most significant factors in elevating contact pressure in the articular cartilage, while the effects of acetabular coverage and changes in the articular cartilage were less significant. The quantification of the pathomechanics of DDH in this study can help identify key mechanical factors that restore normal hip development and can lead to mechanics‐driven treatment options.